Comparative study of two different weighted vests and its effect on joint attention in children with Autism spectrum disorder - K.ALLI, MOT, (pediatrics),; C.CHRISTOPHEL YESHUANA, MOT, (International Journal of Pharma and Bio Sciences, 2017)
To evaluate the effectiveness of weighted vests on joint attention in children with ASD. The objective of this study is to compare the two different weighted vests and its effect on joint attention in children with ASD. Quasi-experimental design was used to find the effectiveness of the study.This study was conducted at corner stone therapy centre and Tiny toods therapy centre, Chennai. Subjects consisted of 14 children with ASD both male and female between 1.5-2years of age. The result shows that there was no replicated treatment effect on JA, but there was slight improvement in experimental group I (5% group), the pre and post test scores showed differences. The result has been consistent with null hypothesis. The weighted vests used in this study may not provide the necessary deep touch pressure input to optimally affect a child’s nervous system as often assumed by occupational therapist. Rigorous research is still needed to explore other sensory regulation treatment methods (e.g., pressure vests) in association with other confounding and interacting factors, which may improve early learning, communication, attention and focus and problem solving competing behaviours for young children with ASD.